2014
DOI: 10.1155/2014/310981
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Amelioration of High-Fat Diet-Induced Fatty Liver by Docosahexaenoic Acid and Lysine Supplementations

Abstract: Fatty liver disease is the most common pathological condition in the liver. Here, we generated high-fat diet-(HFD-) induced nonalcoholic fatty liver disease (NAFLD) in mice and tested the effects of docosahexaenoic acid (DHA) and lysine during a four-week regular chow (RC)feeding. Our results showed that 1% lysine and the combination of 1% lysine + 1% DHA reduced body weight. Moreover, serum triglyceride levels were reduced by 1% DHA and 1% lysine, whereas serum alanine transaminase activity was reduced by 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
(49 reference statements)
0
16
2
Order By: Relevance
“…Many studies have found that purified compounds of plants or fish may improve NAFLD [24][25][26][27]. For example, 6-gingerol is linked to reduced body weight and inhibition of lipid accumulation of hepatocytes in obese mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that purified compounds of plants or fish may improve NAFLD [24][25][26][27]. For example, 6-gingerol is linked to reduced body weight and inhibition of lipid accumulation of hepatocytes in obese mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the lipid content of whole body in the SP100 + Lys and SP100 + P groups further decreased compared to the SP100 group. It has been reported that supplementation of lysine could improve the utilization of amino acids and lead to less lipid storage (Lin et al., ). The declined lipid content of whole body in the SP100 + P group was probably due to that phosphorus accelerated mitochondrial β‐oxidation and reduced the lipid accumulation in fish (Roy & Lall, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional file 1 : Table S1 lists the nutrient composition, energy ratio, and fatty acid compositions in different feedstuff. At the end of 16th week of the study, 12-hour fasted rats were sacrificed with CO 2 suffocate[ 42 ]. Blood was collected into a heparinized tube (6–8 mL) and centrifuged at 1000 × g for 15 min at 4 °C, and plasma was collected and stored at −80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%